Fibroids - Segars, James (Chichester, West Sussex : John Wiley & Sons, 2013)
Fibroids are benign growths of the uterus. They are the most common tumours found in women (20-30% of women), usually in later reproductive years. This book covers evidence-based indications for treatment of uterine fibroids in gynecology, the management of fibroids in pregnancy, surgical treatments and outcomes, rare fibroid syndromes, and more.
Understanding uterine fibroids / Phyllis Leppert, Mazen Fouany, and James Segars -- The clinical spectrum of fibroid disease / Joshua Younger [and others] -- Evidence-based indications for treatment of uterine fibroids in gynecology / James L. Nodler and James H. Segars -- Management of fibroids in pregnancy / Natalie L. Johnson, Errol Norwitz, and James H. Segars -- Management of uterine fibroids in the older woman / Alon Talmor and Beverley J. Vollenhoven -- Medical management of women with symptomatic uterine fibroids / Kristof Chwalisz and Craig A. Winkel -- Nonsurgical option for fibroid treatment : uterine fibroid embolization / Edward Fenlon and James B. Spies -- Magnetic resonance guided focused ultrasound surgery treatment for uterine fibroids / Ronit Machtinger and Fiona M. Fennessy -- Minimally invasive treatment options for uterine fibroids / E. Britton Chahine and William Catherino -- Surgical treatments and outcomes / Ryan J. Heitmann [and others] -- Rare fibroid syndromes / Lisa Marii Cookingham [and others] -- Counseling the patient with uterine fibroids / Gregory M. Christman, Courtney A. Marsh, and Elizabeth J. Campbell.
Includes bibliographical references and index.
Online resource; title from pdf information screen (Ebsco, viewed February 5, 2013).
Keywords: Uterine fibroids; Leiomyoma; Uterine Neoplasms; Leiomyoma; Medicine; Uterus -- Tumors; HEALTH & FITNESS -- Diseases -- Cancer; MEDICAL -- Oncology; Uterine fibroids; Electronic books